2016
DOI: 10.1002/rra.3068
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Natural Flood Management Approaches on In‐Channel Sediment Quality

Abstract: Natural Flood Management (NFM) techniques aim to reduce downstream flooding by storing and slowing the flow of stormwater to river channels. These techniques include a range of measures, including setback stormwater outfalls and the physical restoration of channels and floodplains, to improve the natural functioning of catchments. An additional benefit of NFM measures is the potential reduction in sediment and pollutant delivery to the channel. Urban development releases a variety of heavy metal and nutrient p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…The finding that spatial relationships are nuanced is consistent with the outcomes of other multi‐disciplinary fieldwork performed during the “Clean Water for All” study (Ahilan et al, ; Janes et al, ), which establish that mixed development within subcatchments distributed throughout the catchment of Johnson Creek has produced a fine‐grained mosaic of land‐uses, often exhibiting stark contrasts at subdecimetre scales. In places, surface runoff from industrial sites located adjacent to the mainstream drains directly to Johnson Creek via simple, piped outfalls, with no buffering because urban green spaces are absent and the riparian corridor is nonexistent.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The finding that spatial relationships are nuanced is consistent with the outcomes of other multi‐disciplinary fieldwork performed during the “Clean Water for All” study (Ahilan et al, ; Janes et al, ), which establish that mixed development within subcatchments distributed throughout the catchment of Johnson Creek has produced a fine‐grained mosaic of land‐uses, often exhibiting stark contrasts at subdecimetre scales. In places, surface runoff from industrial sites located adjacent to the mainstream drains directly to Johnson Creek via simple, piped outfalls, with no buffering because urban green spaces are absent and the riparian corridor is nonexistent.…”
Section: Discussionsupporting
confidence: 82%
“…More recently, stream restoration efforts have been implemented at multiple sites along Johnson Creek and its tributaries, involving floodplain reconnection (Ahilan, Guan, Sleigh, Wright, & Chang, 2018;Levell & Chang, 2008), riparian planting, and installation of green infrastructure to trap pollutants in pocket-wetlands and at set-back stormwater outfalls (Janes et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Therefore, it is likely that the average particle size distribution of the sample collected by the PASS and Phillips samplers are representative of the particle size distribution of suspended sediment in Loders Creek during the two sampled events. It should be noted that the Phillips sampler could lose a significant amount of sediment mass (possibly up to 50%) at higher flows (greater than 0.6 m s −1 ), which is not uncommon in most fluvial environments (Droppo & Ongley, ; Horowitz et al, ; Janes et al, ; Ongley et al, ; Vercruysse, Grabowski, & Rickson, ). If the sediment is equally removed from the sampler, this may not adversely affect the particle size distribution of the sample, as demonstrated in Section ; however, it will bias the sample mass collected, thus making the Phillips sampler unsuitable for measuring suspended sediment concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The increased hydraulic roughness in these features causes flow velocities to decrease, encouraging deposition of polluted sediment. Lower pollutant levels were observed at setback outfalls compared with direct outfalls into Johnson Creek (Janes et al, ). River restoration activities (in‐stream and riparian features) along the study reach of Johnson Creek were also found to reduce pollutant levels and create additional benefits such as habitat for species listed as at risk or endangered.…”
Section: Theme 3 Sediment Contaminants Morphology and Riparian Resmentioning
confidence: 99%
“…Higher levels of habitat quality (determined by River Habitat Survey [RHS] assessment methods) and lower levels of channel modification were associated with higher removal efficiency of several pollutants (Fe, Ba, Sn, Mg, P, K). Janes et al () conclude that setback outfalls and river restoration represent passive stormwater treatment measures that reduce the sediment pollutant input into Johnson Creek from the surrounding urban catchment.…”
Section: Theme 3 Sediment Contaminants Morphology and Riparian Resmentioning
confidence: 99%